Stress levels of students pre-Imtihan Syafahi in Islamic boarding school - Wawan Rismawan; Siti Sa’adah Mardiah; Siti Nuraeni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Imtihan Syafahi which has been established by Islamic boarding schools and causes many feelings of stress in female students such as easy headaches, anxiety, lack of concentration in studying, and often angry or aggressive before facing exams. The purpose of this study was to determine the stress level of Santriwati pre Imtihan Syafahi at the Islamic Boarding School. Research Method: This research is a quantitative descriptive type using random sampling. The sample in the study amounted to 74 respondents. Data collection techniques used the DASS 42 questionnaire (Depression Anxiety Stress Scale 42). The results of this study, the category of normal stress levels were 24 students (32.4%), mild stress levels were 17 students (23%), moderate stress levels were 14 students (18.9%), severe stress levels were 12 students (16.2%), very high stress levels weight of 7 students (9.5%). The conclusion from this study is that the majority of respondents are under normal stress and the average age of the respondents is 13 years. Suggestion: For teachers, it is hoped that they can carry out activities to minimize stress such as breathing techniques, hypnotherapy, various games before the Syafahi imtihan. Abstrak: Imtihan syafahi yang telah ditetapkan oleh lembaga pendidikan pesantren dan banyak menimbulkan perasaan stres pada santriwati seperti mudah sakit kepala, gelisah, kurang dapat berkonsentrasi dalam belajar, dan sering marah-marah atau bersikap agresif sebelum menghadapi ujian. Tujuan Penelitian ini untuk mengetahui Tingkat Stres Santriwati pra Imtihan Syafahi di Pondok Pesantren. Metode Penelitian:  Penelitian ini berjenis deskriptif kuantitatif menggunakan random sampling. Sampel dalam penelitian berjumlah 74 responden. Teknik pengumpulan data menggunakan alat kuesioner DASS 42 (Depression Anxiety Stress Scale 42). Hasil Penelitian ini, Kategori tingkat stres normal yaitu sebanyak 24 siswa (32.4%), tingkat stres ringan17 siswa (23%), tingkat stres sedang14 siswa (18.9%), tingkat stres berat12 siswa (16.2%), tingkat stres sangat berat7 siswa (9.5%). Kesimpulan dari penelitian iniMayoritas responden berada pada stres normal dan rerata umur responden adalah 13 tahun. Saran: Bagi guru, diharapkan dapat melakukan aktivitas untuk meminimalisir stres seperti teknik napas, hypnoterapi berbagai permainan sebelum imtihan syafahi.